Multi-Charge Storage Layer Model of High-Charge-Density Triboelectric Nanogenerator - Xin Cui; Yaming Zhang; Yan Zhang (Nanoenergy Advances, 2023)
Triboelectric nanogenerators (TENGs) are key technologies for the Internet of Things with energy harvesting. To improve energy conversion efficiency and convert mechanical energy into electrical energy, high charge density in TENGs plays a crucial role in the design of triboelectric materials and device structures. This paper proposes mechanisms and strategies to increase TENGs’ charge density through multi-charge storage layers. We also discuss the realization of higher charge densities through material and structure design. The implementation of novel charge storage strategies holds the potential for significant improvements in charge density.